Chiral, crosslinked, and micron-sized spheres of substituted polyacetylene prepared by precipitation polymerization. (14th March 2018) - Huang, Huajun; Wang, Huilei; Wu, Youping; Shi, Yan; Deng, Jianping
Abstract: Owing to the ever-rising importance of chirality, chiral polymeric spheres are becoming especially attractive for both chirality and material scientists. The microspheres consisting of helical polymers, e.g. substituted polyacetylenes, are particularly intriguing because their chirality not only originates in pendant chiral groups, but also originates in one-handed helical polymer backbones. Unfortunately, the size of such spheres is limited, and their crosslinking is a huge challenge; specifically, preparing chiral crosslinked microspheres (CCMs ) of substituted polyacetylenes with diameter of 1–50 μm remains as an intractable task. In this work, such CCMs (with diameters of 1.3–2.3 μm) were successfully prepared for the first time through precipitation polymerization. Circular dichroism and UV-vis absorption spectra demonstrate that the chirality of CCMs not only simply originates in the monomer units, but also originates in the chirally helical structures of the polymer. The CCMs thus have the potential to be applied as chiral stationary phase for high-performance liquid chromatography. Based on macroscopic and microscopic observations, a mechanism for the precipitation polymerization of acetylenic monomers in the presence of crosslinker is proposed. The present study provides new opportunities for designing and synthesizing functional CCMs constructed from helical polymers. Graphical abstract: Highlights: Chiral crosslinked spheres of substituted polyacetylene were successfully prepared. Spheres with diameters of 1.3–2.3 μm were obtained from precipitation polymerization. The polymer in these microspheres can form chirally helical structure. The microspheres are suitable for being applied as chiral stationary phase for HPLC. A mechanism for this novel precipitation polymerization was proposed.